2003
DOI: 10.1037/0735-7044.117.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of human amygdala activity during Pavlovian fear conditioning: Stimulus processing versus response expression.

Abstract: Although laboratory animal studies have shown that the amygdala plays multiple roles in conditional fear, less is known about the human amygdala. Human subjects were trained in a Pavlovian fear conditioning paradigm during functional magnetic resonance imaging (fMRI). Brain activity maps correlated with reference waveforms representing the temporal pattern of visual conditional stimuli (CSs) and subject-derived autonomic responses were compared. Subjects receiving paired CS-shock presentations showed greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
116
4
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 51 publications
16
116
4
1
Order By: Relevance
“…The unilateral findings in both experiments were largely consistent with previous neuroimaging studies of fear conditioning (Büchel et al, 1998;Cheng et al, 2003;LaBar et al, 1998). However, left amygdala activity during fear learning has also been reported (Morris, Ohman, & Dolan, 1998;Phelps et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The unilateral findings in both experiments were largely consistent with previous neuroimaging studies of fear conditioning (Büchel et al, 1998;Cheng et al, 2003;LaBar et al, 1998). However, left amygdala activity during fear learning has also been reported (Morris, Ohman, & Dolan, 1998;Phelps et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this view, one study from our laboratory (Cheng at al., 2003), conducted with an analytical approach emphasizing sensitivity to the response-generating functions of the amygdala, found significant amygdala activity, whereas another study (Knight, Cheng, Smith, Stein, & Helmstetter, 2004a) involving a more traditional analysis technique and focusing on stimulusprocessing properties of the amygdala, failed to detect differential amygdala activity. The current article revisited this data set that failed to show significant amygdala activity (Knight et al, 2004a) in order to determine whether activity within this region can be better predicted by an analytical approach emphasizing response expression.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…First, as Bernier and colleagues point out, such studies contribute to our understanding of the neuropathology underlying this spectrum of disorders. Extensive animal (see LeDoux, 1994LeDoux, , 1995LeDoux, , 1998LeDoux, , 2000 for detailed reviews) and human (Bechara, Tranel, Damasio, Adolphs, Rockland & Damasio, 1995;Büchel, Morris, Dolan & Friston, 1998;Büchel, Dolan, Armony & Friston, 1999;Cheng, Knight, Stein & Smith, 2003;Knight, Smith, Cheng & Stein, 2004;LaBar, LeDoux, Spencer & Phelps, 1995;LaBar, Gatenby, Gore, LeDoux & Phelps, 1998;Morris, Őhman & Dolan, 1997;Morris, Friston & Dolan, 1997Phelps, LaBar, Anderson, O'Connor, Fulbright & Spencer, 1998) research has demonstrated that the associative learning in fear conditioning paradigms is mediated by the amygdala, a limbic structure which has attracted increasing attention in relation to ASD in recent years. Although several lines of research have implicated the amygdala in the pathology underlying this disorder (e.g.…”
Section: Introductionmentioning
confidence: 99%